(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: India is the second most populated country across the world. Around the world 3, 85,000 babies are born per day. In India the current population are 140 crore. To overcome the growth of population the health care system also delivers the family planning methods in community to stabilize the population. The programmes like Reproductive Child Health Programme, Maternal Child Health Programme and Family Welfare Programme also have taken a recommendation to improve the health of mothers, children and also family members and also they educate about the Family Planning Method. India has adopted the goal of two children norms. In Gujarat there are 6.55 crore population and per 1000 people there are 17.163 births.Aim: The main aim of this study was to assess the effectiveness of education package regarding selected contraceptive methods and to control the growth of population by educating the community peoples at some extent.Objectives: To assess the pre-test and post-test knowledge, attitude and utilization score regarding selected contraceptive methods among postnatal mothers. To evaluate the effectiveness of educational package. To correlate the relationship between knowledge, and attitude.To associate the mean difference before and after the level of knowledge, and attitude.Methodology: The pre-experimental one group pre-test and post-test design was adopted.The 60 postnatal mothers were selected as a sample from various selected PHC of Kheda District by non-probability convenient sampling technique. The written setting permission was taken from the medical officer of PHC for data collection. The prior consent form was also signed by the postnatal mothers for the study. The tool was developed by four sections:Section I: Socio-Demographic Data.Section II: Structured Knowledge Questionnaires.Section III: Likert Attitude Scale.Section IV: Checklist Questionnaires for Utilization.The data were analyzed by using the SPSS Software. The frequency and percentage distribution are used to assess the demographic variables and the mean and standard deviation are used to describe the knowledge, attitude and utilization regarding contraceptive methods. The paired t-test was used to compare pre and post test score, Karl Pearson correlation formula was used to correlate the pre-test level and Chisquare test was used to determine the association between mean differences.Results: Out of 60 samples,41.7 % (25)belong to age 18-22 years, 100% (60) belong to Hindu religion, 48.3% (29) was not formal educated, 90.0% (54) was housewife, 31.7% (19) belong to 4-6 years duration of marriage, 50.0% (30) have one child, 86.7% (52) have no history of abortion, 75.0% (45) got information related to contraceptive method from Health Personnel. Thepaired t-test value was 15.14, 9.26 and 13.13. Hence, there exists significance effectiveness on level of knowledge, and attitudebefore and after administration of educational package among postnatal mothers.There was positive correlation between knowledge, and attitude (r = 0.65), and found no significant relationship between all the variables regarding selected contraceptive methods after educational package among postnatal mothers.Conclusion: The study concludes that after the intervention, 47% (28) mothers had moderately adequate knowledge, none of them had inadequate knowledge and 53% (32) had adequate knowledge regarding contraceptive method.37% (22) mother had moderately favourable attitude, none of them had unfavourable attitude, and 63% (38) mother had favourable attitude regarding contraceptive method.